BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2003)
Implications of Plant Diseases on Produce Quality. Dr. D.P. Singh (ISBN-81-272-0777-2) Kalyani Publishers, 4779/ 23, Ansari Road, Daryaganj, New Delhi 110 002; 2003; pp 197, Price Rs. 225/-